2019
DOI: 10.1002/ptr.6546
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin: Possible uses in the prevention and treatment of mixed osteoarthritic pain

Abstract: Osteoarthritis (OA) pain has been proposed to be a mixed pain state, because in some patients, central nervous system factors are superimposed upon the more traditional peripheral factors. In addition, a considerable amount of preclinical and clinical evidence has shown that, accompanying the central neuroplasticity changes and partially driven by a peripheral nociceptive input, a real neuropathic component occurs that are particularly linked to disease severity and progression. Hence, innovative strategies ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 208 publications
0
8
0
Order By: Relevance
“…It was reported that LPS could contribute to low-grade cell inflammation (Huang and Kraus, 2016), while OA is exactly the low-grade inflammatory state mentioned above. Besides, previous investigations have demonstrated that MF was a xanthonoid with anti-inflammatory capacity, and it was reported to be a promising therapeutic drug for OA (Luczkiewicz et al, 2014;Saha et al, 2016;Qu et al, 2017b;Garrido-Suarez and Garrido, 2019). Previous investigations elucidated that MF markedly suppressed the productions of IL-6, IL-1b, and TNF-a in LPS-triggered primary hepatocytes, BALB/c mice mammary gland, and peritoneal macrophages (Jeong et al, 2014;Pan et al, 2016;Qu et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that LPS could contribute to low-grade cell inflammation (Huang and Kraus, 2016), while OA is exactly the low-grade inflammatory state mentioned above. Besides, previous investigations have demonstrated that MF was a xanthonoid with anti-inflammatory capacity, and it was reported to be a promising therapeutic drug for OA (Luczkiewicz et al, 2014;Saha et al, 2016;Qu et al, 2017b;Garrido-Suarez and Garrido, 2019). Previous investigations elucidated that MF markedly suppressed the productions of IL-6, IL-1b, and TNF-a in LPS-triggered primary hepatocytes, BALB/c mice mammary gland, and peritoneal macrophages (Jeong et al, 2014;Pan et al, 2016;Qu et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have already been conducted to investigate the influences of MF on bone-related diseases. For example, MF was reported to be effective in the treatment and prevention of mixed osteoarthritic pain (Garrido-Suarez and Garrido, 2019). Besides, an earlier literature clarified that MF exhibited anti-osteoclastogenic effects in the prevention and treatment of bone diseases, such as osteoporosis, erosive arthritis, and so on (Ang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Secoiridiods are characteristic substances of MR, while their contents are very low. Studies have indicated that secoiridiod glycosides possess wide biological activities such as anti-inflammatory and immunoregulatory (Saravanan et al, 2014a;Saravanan et al, 2014b;Wang et al, 2019a), analgesic (Liu et al, 2016;Garrido-Suárez et al, 2020), anti-tumor (Shao et al, 2017;Wu et al, 2017), hypoglycemic (Vaidya et al, 2013aDhanavathy, 2015;Vaidya et al, 2012;Vaidya et al, 2009), neuroprotective (Wang et al, 2019b;Wu et al, 2019) effects. Currently, about 20 iridoids secoiridoids (1~20) have been isolated from MR (Ma et al, 1996;Xu et al, 2008;Yao, 2013;Pan et al, 2015).…”
Section: Iridoids and Secoiridoidsmentioning
confidence: 99%
“…Recently, Garrido-Suárez et al (2020) proposed therapeutic potential of MAF as a multi-targeted compound in mixed OA pain based on three main aspects including the preclinical evidence of this xanthone, applications of formulas containing MAF in some preliminary clinical studies on musculoskeletal or neuropathic pain, and speculations regarding its possible mechanism of action in accordance with research advances in OA pain.…”
Section: Antinociceptive Effectsmentioning
confidence: 99%
“…Mangiferin (2‐β‐D‐glucopyranosyl‐1,3,6,7‐tetrahydroxy‐[9H]‐xanthen‐9‐one) was first isolated from mango leaves, and it has been documented its analgesic, anti‐inflammatory, antioxidant, neuroprotective, and immunomodulatory properties (Garrido‐Suárez, Garrido, Piñeros, & Delgado‐Hernández, 2020; Imran et al, 2017). A number of secondary substances in many classes such as phenolic acids, flavonoids, terpenoids, and carotenoids have also been isolated from the extracts from various parts of mango plants such as leaves, roots, bark, flowers, fruits, and seeds (Table 3).…”
Section: Phytotoxic Substances In Mangomentioning
confidence: 99%